The logistic technique in the toyotism: a geographic approach on Just-in-Time - Carvalho, André Simplício (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2017)
The Just-in-Time, among other logistical systems, it is much quoted by geographers dedicated to economic and transportation studies, especially in the context of Toyotism, but very little understood. Thus, we propose in this article explain what exactly Just-in-Time is, contextualizing it in the heart of the production process changes that allowed the consolidation of globalization since the 1970s, to thereby provide a geographical approach on the same. This approach allows to interpret the Just-in-Time as a flow planning technique that reveals itself in space as a network. Network this orientate to a zero waste production.